Perception on Building Cultural Responsiveness through ‎the Synergy of Maqasid al-Shariah and Rahmatan Lil ‎‎'Alamin in Islamic Academia - Idris, T; Ramli, Syahrur; Iswantir; Akbar, M. Rafi; Darmawan, Aidil (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study examines cultural responsiveness through the synergy of Maqashid al-Shariah and Rahmatan Lil 'Alamin for university students. Empirical data indicate that consistent religious practice has decreased to 50.5%, despite the widespread adoption of moderation. This gap is exacerbated by cognitive repetition and a disconnect between theoretical concepts and the realities of campus life. As a result, religious literacy remains stagnant and fails to translate into meaningful social “praxis.” To address this issue, a systemic reorientation is proposed, utilizing Jasser Auda's Maqashid al-Shariah framework as an adaptive value filter to navigate modern cultural disruptions. This study employs a qualitative descriptive design, grounded in a humanistic systems approach, to explore student perceptions. The primary subjects are PAI (Islamic Religious Education) students at Universitas Islam Negeri Mahmud Yunus Batusangkar. Data were collected through reflective interviews and observations, and analyzed using the Miles and Huberman model. The findings show that students frequently adopt hedonistic digital trends, such as “cultural show-offs,” rather than religious principles for social validation. While 53.6% recognize the fundamental right to worship, maintaining consistency in religious practice remains a challenge amidst academic pressures. Additionally, participants exhibited 60.8% social empathy but lacked effective religious coping mechanisms to manage the psychological stress of culture shock. Despite their strong academic focus, 84.5% of students acknowledge the need for critical religious literacy to effectively filter misinformation in the digital world. This study highlights that synergizing Maqashid al-Shariah with Rahmatan Lil 'Alamin offers a robust defense against moral decline and radicalism. Ultimately, this framework revitalizes Islamic education, transforming it into a dynamic guide for promoting universal well-being and inclusive social harmony.